2009
DOI: 10.3176/eco.2009.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of mice and voles withIxodes ricinusticks in Lithuania and Norway

Abstract: Abstract.A total of 693 small rodents were live-trapped in Lithuania and Norway. In Lithuania, the mice Apodemus flavicollis and A. agrarius were more frequently infested with ticks than the voles Microtus arvalis and Myodes glareolus. The overall prevalence of infestation with Ixodes ricinus in different sampling locations of Lithuania ranged for A. flavicollis from 0% to 92.3%, for M. glareolus from 5.9% to 100%, and for M. arvalis from 0% to 37.8%. In Norwegian sites the prevalence of infestation was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In the present study, examined A. flavicollis, M. glareolus and M. minutus rodents were infested with I. ricinus ticks, the main vector for R. helvetica. In previous studies conducted in Lithuania, it has been shown that A. flavicollis mice and M. glareolus voles are frequently infested with immature I. ricinus ticks, with a higher prevalence of infestation detected in A. flavicollis [25] .…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, examined A. flavicollis, M. glareolus and M. minutus rodents were infested with I. ricinus ticks, the main vector for R. helvetica. In previous studies conducted in Lithuania, it has been shown that A. flavicollis mice and M. glareolus voles are frequently infested with immature I. ricinus ticks, with a higher prevalence of infestation detected in A. flavicollis [25] .…”
Section: Discussionmentioning
confidence: 92%
“…This type of behaviour reflects physiological adaptation of D. marginatus to conditions of limited access to the food source. Co-parasitism of various tick species on the same animals [ 13 ] and humans [ 14 ] has been reported in natural conditions. In Spain, 9 % of 3685 patients infested by ticks were attacked by two or a greater number of species [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The time pattern of infestation of small rodents by immature ticks might be the combined result of the effects of factors associated with both the parasites, and the hosts (Rosà et al, 2007;Paulauskas et al, 2009;Paziewska et al, 2010;Pérez et al, 2012;Estrada-Peña et al, 2013). As a consequence, conclusions on seasonal activity of ticks, based upon rodent infestation, must be drawn with caution.…”
Section: Discussionmentioning
confidence: 99%